Litotoponímia mineira - Maryelle Joelma Cordeiro (2018)
By studying toponymy, it was possible to highlight traces of the socio-cultural history of a people, to show characteristics not only of the physical environment, and also to contribute to the preservation of the societys memory. The toponym can be seen as the historical residue of the presence of a people in a certain place, which resists as a witness of their history and language, preserving and showing, in its linguistic signs, the contact between the man and the environment in which he lives. Toponyms of mineral origin, i.e. litotoponyms, have in their morphic structure a relation to the constitution of the soil and to important moments in the life and history of a community. This work aims at carrying out a linguistic and cultural study of contemporary litotoponyms, collected from the Projeto Atlas Toponímico do Estado de Minas Gerais ATEMIG (Minas Gerais state Toponymic Atlas Project), coordinated by Prof. Maria Cândida Trindade Costa de Seabra. It also includes historical litotoponyms that named landforms in the Captaincy of Minas Gerais in the XVIII and XIX centuries, made available by repository of the project Registros Cartográficos Históricos: Revelando o Patrimônio Toponímico de Minas Gerais do Período Colonial ao Joanino, (Historical Cartographic Registers: Revealing the Toponymic Heritage of Minas Gerais from the Colonial to the Joanine Period) coordinated by Prof. Maria Cândida Trindade Costa de Seabra and Prof. Márcia Maria Duarte dos Santos, from UFMG. The theoretical-methodological framework used is based on the toponymic models of Dauzat (1926), Dick (1990a, 1990b) and Seabra (2004). Thus, the study of the litotoponymic lexicon gives us a rich selection of data on the toponymy of Minas Gerais, besides revealing evidence of the linguistic past of Minas Gerais and increasing the knowledge on the culture and history of the people of Minas Gerais.